THE USE OF FIVES STRATEGY TO TEACH READING COMPREHENSION FOR ELEVENTH GRADERS - Sari, Septika; Oktaviani, Ayu; Yulfi, Yulfi (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
One of the objectives that should be developed in teaching is reading comprehension skills. In fact, many students still have a lot of problems with reading. Therefore, teachers should use specific strategies in teaching reading comprehension to resolve students’ difficulties. The purpose of the research was to find out whether or not it is significantly effective to teach reading comprehension by using the FIVES strategy for eleventh-grade students of SMA Negeri 2 Lubuklinggau. This research applied the pre-experimental method with one group pre- and post-test only. The population of the study was all of the eleventh-grade students of SMA Negeri 2 Lubuklinggau. Cluster random sampling was taken to take the sample class. Class XI MIA 4 was chosen as the sample class. The data was collected through a reading test consisted of 20 items of multiple-choice form. The results of this research were: 1) the average score in the pre-test was 61.81, and the post-test was 78.06, 2) the result of the Paired t-test was 10.167, which higher than t-table (1.689) at the significant level of 5% with df 35. Therefore, the alternative hypotheses (Ha) was accepted. It means that it was significantly effective to teach reading comprehension by using the FIVES strategy for eleventh-grade students of SMA Negeri 2 Lubuklinggau.